Ingmar Bergman: Deus, dúvida e conflito no cinema - Rodrigues, Fabiana (2018)
This research deals with the relationship between the sacred and the profane in the Trilogy of silence, by the Swedish filmmaker Irgman Bergman, represented by the films: Säson i em spegel – Through a Glass Darkly (1961); Nattvardsgäterna – Winter Light (1961) and Tystnaden – The Silence (1962). Subsequently, the term Tetralogy of silence is proposed, since the film Jungfrukällan – The Virgin Spring (1959) is aggregates to the Trilogy of silence. The analysis concerns the dialogue between the sacred and the profane, verifying not only the opposition present in these conceptions, but understanding these definitions as a film strategy, at a continuous pace of union and rupture, demonstrating the relevance to understand this strategy as an allegorical category. Both the order of the sacred and the order of the profane present sense disturbances, reinforcing the scenic creation in Bergman‟s film discourse. Therefore, as a theoretical support to substantiate the concepts of sacred/profane and allegory, the authors Mircea Elíade and Umberto Eco, Sören Kierkegaard and Jean-Paul Sartre were utilized in relation to the problem of the anguish, the despair and the existential character of the human being; to the cinematographic discourse context, corroborate the theories of Jacques Aumont and Ismail Xavier, among other references.